Implementation of Sharia Business Ethics in Ijarah Financing for Islamic Banking Sustainability - Aditha Naya; Rahmayati Rahmayati (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2026)
The rapid expansion of Islamic banking underscores the need to integrate Sharia business ethics with sustainability principles, positioning ijarah-based financing as a pivotal mechanism for ensuring fairness and transparency in asset utilization. Despite its normative strength, a persistent gap exists between the conceptual framework of Sharia business ethics and its practical application. This study investigates the values of Sharia business ethics, explores the implementation of ijarah financing, evaluates the alignment between theory and practice, and examines the role of ijarah in advancing sustainability within Islamic banking. Employing a qualitative case study approach, the research was conducted at the Medan-Serdang Branch Office of Bank Sumut. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing. Thematic findings reveal that institutional practices of honesty, fairness, transparency, and trustworthiness are embedded in ijarah financing, particularly through the ijarah muntahiyah bittamlik scheme. However, limited customer understanding of Sharia business ethics perpetuates a gap between normative ideals and practice. The study concludes that ijarah financing contributes to sustainability by fostering productive economic activities, expanding equitable access to financing, and strengthening public trust. These findings imply that enhancing Islamic financial literacy and internalizing ethical values are critical to optimizing the sustainability impact of Islamic banking.